Diversity and distribution of true bugs (hemiptera) in UiTM Negeri Sembilan (Kuala Pilah Campus), Negeri Sembilan / Rabiah Adawiah Abdul Ghani - Abdul Ghani, Rabiah Adawiah (Faculty of Applied Sciences, 2015)
This study of diversity and distribution of Hemiptera in UiTM Negeri Sembilan (Kuala Pilah Campus),Negeri Sembilan is aim to record species of Hemiptera at UiTM Negeri Sembilan (Kuala Pilah Campus) and also to determine the diversity and distribution of Hemiptera at UiTM Negeri Sembilan (Kuala Pilah Campus). Three different study sites has been identified which site 1 (open area), site 2 (forest margin), and site 3 (forest). The trapping method used at study sites were window traps, pitfall traps, light traps, yellow pan traps and direct collection. 12 familes of Hemiptera found at three different study sites were Scutelleridae, Reduviidae, Alydidae, Largidae, Pentatomidae, Coreidae, Hydrometridae, Cicadellidae, Cicadidae, Flatidae, Cercopidae and Aphididae. There were 18 individuals from 6 species recorded at site 1, 47 individuals from 6 species at site 2 and 53 individual from 9 species at site 3. Largidae have the most species in site 1, whereas Cicadellidae shows the largest percentage of existence in site 2 and site 3. By using Shannon-Weiner Diversity Index, site 3 had shown more diverse (H‟=1.48) compared with site 2 (H‟=1.44) and site 1 (H‟=1.45). For species evenness, site 1 (E=0.81) have highest evenness index followed by site 2 (E=0.74) and site 3 (E=0.67). While for Richness index, site 3 showed the highest richness species (R=2.01) followed by site 1 (R=1.73) and the least site 2 (R=1.59). The Sorensen Similarities Index showed (site 2 and site 3) has the highest species composition where S=0.97, followed by (site 1 and site 3) with S=0.69, at the least species composition between two sample was (site 1 and site 2) with S=0.57.